Pengaruh Penggunaan Media Booklet terhadap Pengetahuan dan Sikap Ibu tentang Perkembangan Anak Usia 3-5 Tahun di Puskesmas Pupuan I Tabanan - Ni Nyoman Ayu Trisya Utari; Ni Made Ayu Yulia Raswati Teja; Putu Ayu Ratna Darmayanti (Universitas Malahayati Lampung, 2026)
ABSTRACT The increasing incidence of children with developmental delays can be related to various factors, one being the insufficient awareness of parents regarding child development, which reduces their ability to give appropriate stimulation and identify delays in growth and development. Implementing booklet media for health education on child development is an effective method to improve the understanding and attitudes of women regarding this issue. To determine the effect of the implementation of booklet media on mothers' knowledge and attitudes about the development of toddlers aged 3-5 years at public health center Pupuan I. This study employed a pre-experimental design featuring a one-group pretest-posttest approach. There were 170 mothers who had toddlers aged 3-5 years at the public health center Pupuan recruited as a sample of the study. The data were analyzed using the Wilcoxon test.The findings showed that the average of the pretest was 64.50 (moderate knowledge), which increased to 76.88 (good knowledge). The average attitude of the pretest was 65.94 (negative attitude), which increased to 73.66, an increase of 7.72 points (positive attitude). There was a difference in the knowledge and attitude of mothers before and after being given a booklet media intervention with a p-value of 0.00 (0.05). In the attitude variable, the obtained p-value was 0.00 (0.05). There is an effect of booklet media on the knowledge and attitude of mothers about the development of toddlers aged 3-5 years at public health center Pupuan I. Keywords: Toddlers aged 3-5, Booklet, Knowledge, Development, Attitude. ABSTRAK Tingginya kasus anak yang mengalami keterlambatan perkembangan disebabkan oleh beberapa faktor, salah satunya pengetahuan orang tua yang kurang tentang tumbuh kembang anak. Sehingga, kurang memberikan stimulasi dan mendeteksi adanya keterlambatan tumbuh kembang. Pendidikan kesehatan tentang tumbuh kembang anak dengan media booklet menjadi solusi dalam meningkatkan pengetahuan dan sikap ibu tentang tumbuh kembang anak. Tujuan penelitian ini untuk mengetahui pengaruh penggunaan media booklet terhadap pengetahuan dan sikap ibu tentang perkembangan anak usia 3-5 tahun di Puskesmas Pupuan I. Jenis penelitian ini pre-eksperimental menggunakan rancangan one group pretest-posttest. Jumlah sampel yang digunakan yaitu 170 ibu yang memiliki balita berusia 3-5 tahun di wilayah kerja UPTD Puskesmas Pupuan I. Analisa data yang digunakan adalah uji Wilcoxon. Rata-rata pada saat pretest sebesar 64,50 (pengetahuan cukup) meningkat menjadi 76,88 (pengetahuan baik). rata rata sikap pada saat pretest sebesar 65,94 (sikap negatif) meningkat menjadi 73,66 peningkatan sebesar 7,72 poin (sikap positif). Terdapat perbedaan bahwa pengetahuan dan sikap ibu sebelum dan sesudah diberikan intervensi media booklet dengan p-value 0,00 (0,05). Pada variabel sikap diperoleh p-value 0.00 (0,05). Terdapat pengaruh dari media booklet terhadap pengetahuan dan sikap ibu tentang perkembangan anak usia 3-5 tahun di Puskesmas Pupuan I. Kata Kunci: Balita, Booklet, Pengetahuan, Perkembangan, Sikap.